Grain Drying in a Paraboloid-Based Spouted Bed with and without Draft Tube - Evin, Duygu; Gul, Hasan; Tanyildizi, Vedat (Taylor & Francis Inc, 2008)
In this study, grain drying in a spherical-based spouted bed (SBSB), a cone-based spouted bed (CBSB), and a paraboloid-based spouted bed (PBSB) with and without draft tube was investigated. Spouted-bed bases with the same volume in different shapesspherical, cone, and paraboloidwere used for the drying experiments to investigate the effect of the spouted-bed base shape on drying. The drying experiments were carried out with perforated and solid draft tubes. The effects of the distance between the gas inlet nozzle and the bottom of the draft tube (entrainment zone height) and the draft tube diameter as geometric parameters on drying were also investigated. It was seen that the geometrical shape of the contactor base influenced the drying time. The highest drying rate was achieved for drying in a paraboloid-based spouted bed. The results also showed that using a draft tube caused a significant increase in drying time. Because the perforated draft tube allows a higher gas flow rate through the annulus, it decreases the drying time when compared with the solid draft tube. Drying time decreased slightly with the decreasing height of the entrainment zone but draft tube diameter did not have a considerable effect on drying.
Keywords: Draft tube; Grain drying; Paraboloid base; Spouted bed